Computed Tomography Pulmonary Angiography (CTPA) data - Sjöblom, Tobias; Sladoje, Nataša; Kahraman, Ali Teymur; Toumpanakis, Dimitris; Fröding, Tomas (AIDA Data Hub, 2019)
30 clinical routine CTPA examinations, performed on a Philips Brilliance 64 CT or GE Lightspeed VCT. 14317 axial images (1 or 0,625mm) plus additional reformats. 5 of the CTPAs are positive for pulmonary embolism and have all the emboli carefully delineated by an experienced radiologist.
Keywords: Radiology; Computed tomography; Thorax; Pulmonary embolism; Annotated; Medical and Health Sciences; Medicin och hälsovetenskap; Radiology and Medical Imaging; Radiologi och bildbehandling